2020
DOI: 10.1177/0003134820982560
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Presentations of Acute Diverticulitis During COVID-19 Pandemic may be More Likely to Require Surgery due to Increased Severity: A Single-Centre Experience

Abstract: Background The novel coronavirus disease 2019 (COVID-19) pandemic has resulted in fewer emergency presentations of many acute medical and surgical conditions. The purpose of this study was to assess the severity of disease at presentation and quantify the change in number of presentations during this period. Methods This retrospective study includes all patients diagnosed with acute diverticulitis on abdominopelvic computerised tomography (CT) between March 1, 2020 and June 30, 2020, compared to the same perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…More severe symptoms due to delayed access to hospital care have been reported in the pediatric population [4] and acute coronary syndrome cases [10,35]. Increased disease severity has also been described for abdominal conditions, with an increase of complicated cases among patients with diverticulitis [22,24,25] and acute appendicitis [23,36]. Cano-Valderaama [32] reported a statistically significant increase of time from symptom onset to ED presentation among patients with acute surgical conditions, leading to higher Sequential Organ Failure Assessment (SOFA) scores, lower laparoscopic interventions, higher morbidity, and longer lengths of stay, while Tartaglia et al reported a higher percentage of patients requiring ICU admission during the pandemic [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More severe symptoms due to delayed access to hospital care have been reported in the pediatric population [4] and acute coronary syndrome cases [10,35]. Increased disease severity has also been described for abdominal conditions, with an increase of complicated cases among patients with diverticulitis [22,24,25] and acute appendicitis [23,36]. Cano-Valderaama [32] reported a statistically significant increase of time from symptom onset to ED presentation among patients with acute surgical conditions, leading to higher Sequential Organ Failure Assessment (SOFA) scores, lower laparoscopic interventions, higher morbidity, and longer lengths of stay, while Tartaglia et al reported a higher percentage of patients requiring ICU admission during the pandemic [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these kinds of urgent conditions often lead to surgical resection of the involved organ, enabling an assessment of the pathological findings to investigate whether and to what extent COVID-19-induced delays have really increased disease severity. Previous retrospective observational studies [21][22][23] reported a reduction of ED admissions for abdominal surgical emergencies during the COVID-19 infection waves, also suggesting an increase of disease severity at presentation based on clinical [24] and radiological [21][22][23][24][25] data, but an analysis and correlation with pathological findings is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…The initial search produced 135 potentially relevant articles. After 85 articles were screened for relevance of titles and abstracts, 50 full text articles were further assessed for eligibility and 25 were excluded ( Supplementary Table S1 ); thus, 25 trials were included in the review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Their characteristics are reported in Table 1 , Table 2 , Table 3 and Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…One of these diseases is colonic diverticular disease, with a variable spectrum from asymptomatic diverticulosis to acute diverticulitis up to peritonitis and abscess formation [ 7 ]. Compared to previous years, during the COVID-19 pandemic we have observed an increase in severe forms of diverticulitis in the emergency rooms [ 9 ], often with complications such as abdominal abscesses or purulent/fecal peritonitis [ 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Welle im Jahr 2020 in London ebenfalls ein Rückgang von Patientenvorstellungen um ca. 50 % berichtet mit einem Trend hin zu komplizierteren Typen mit Abszess oder Perforation [ 15 ].…”
Section: Notfallchirurgieunclassified